The role of small specimen creep testing within a life assessment framework for high temperature power plant. (17th February 2018) - Morris, A.; Cacciapuoti, B.; Sun, W.
ABSTRACT: The safe operation of ageing materials and structures operating at high temperature and pressure is challenging. This paper, for the first time, clearly addresses the role of small specimen creep testing methods within a practical life assessment framework, with a case study used to illustrate the main principles and applications. To enhance the current practice for assessing the condition of creep ageing components, more proactive use of small specimen testing methods is proposed for the in-service condition assessment of power plant materials, earlier in the plant lifecycle and within a holistic life assessment framework. The paper describes how small specimen creep testing methods and other complementary tools can be used together in a new structured approach to life management. There is a clear need to provide the plant owner with more reliable and effective life prediction tools, based on earlier and more rigorous assessment of in-service life consumption. A novel, holistic, life assessment methodology including the use of small specimen creep testing has been developed by the authors.